Project Based Learning Berbantuan Aplikasi Tiktok Sebagai Media Pembelajaran IPS Inovatif - Feby Nurliana; Sriyanto Sriyanto (UM Purwokerto Press, 2022)
Along with the declaration of the industrial revolution 4.0, the dynamics of learning can no longer implement conventional methods, especially in the selection of learning models and media. Project based learning assisted by the Tik Tok application can be an attractive learning solution for students. Although the Tik Tok application comes with a negative predicate from the community, on average, generation Z children now really enjoy this application. But if the Tik Tok application is used properly, it will be an interesting learning medium. The purpose of this study is to find out that project based learning assisted by the tik tok application media can improve students' creative thinking in social studies learning. The researcher uses a qualitative method in the form of Research and Development (R & D), namely research that is followed up with the development and dissemination of a learning media through the cycle process of Action, Reflection, Evaluation, Replication, and Innovation. The subjects of this study were students of class VIII B SMP Negeri 3 Kawunganten Cilacap, totaling 30 students. Data collection techniques used are observation, interview and documentation techniques. While the data analysis technique is qualitative analysis to determine the increase in students' creative thinking. The instrument is used to see the creative thinking ability of class VIIIB students during social studies learning. From observations on 30 students that have been carried out, it shows that for the very high category there are 16 students, for the high category 8 students, for the medium category 4 students, for the low category 2 students. From these data, the findings obtained are that social studies learning with project based learning assisted by the tik tok application media can run well and can increase the creativity of students.